CT-Based Peritumoral and Intratumoral Radiomics as Pretreatment Predictors of Atypical Responses to Immune Checkpoint Inhibitor Across Tumor Types: A Preliminary Multicenter Study - He, Shuai; Feng, Yuqing; Lin, Qi; Wang, Lihua; Wei, Lijun; Tong, Jing; Zhang, Yuwei; Liu, Ying; Ye, Zhaoxiang; Guo, Yan; Yu, Tao; Luo, Yahong (Frontiers in Oncology, 2021)
Objective: To develop and validate radiomics based on intra- and peri-tumoral regions using pretreatment CT imaging for prediction of atypical responses to immune checkpoint inhibitor (ICI) in cancer patients. Methods: In total, 135 patients derived from five hospitals with pathologically confirmed malignancies receiving ICI were included in this retrospective study. Atypical responses including pseudoprogression (PsP) and hyperprogression disease (HPD) were identified as their definitions. A subgroup of standard progression disease (sPD) in 2018 was also involved in this study. Based on pretreatment CT imaging, a total of 107 features were extracted from intra- and peri-tumoral regions respectively. The least absolute shrinkage and selection operator (Lasso) algorithm was used for feature selection, multivariate logistic analysis was used to develop radiomics signature (RS). Finally, a total of nine RSs, derived from intra-tumoral, peri-tumoral and combination of both regions, were built respectively to distinguish PsP vs HPD, PsP vs sPD, and HPD vs sPD. The performance of the RSs were evaluated with discrimination, calibration, and clinical usefulness. Results: No significant difference was found when compared in terms of clinical characteristics of PsP, HPD, and sPD. RS based on combined regions outperformed those from either intra-tumoral or peri-tumoral alone, yielding an AUC (accuracy) of 0.834 (0.827) for PsP vs HPD, 0.923 (0.868) for PsP vs sPD, and 0.959 (0.894) for HPD vs sPD in the training dataset, and 0.835 (0.794) for PsP vs HPD, 0.919 (0.867) for PsP vs sPD, and 0.933 (0.842) for HPD vs sPD in the testing dataset. The combined RS showed good fitness (Hosmer-Lemeshow test P>0.05) and provided more net benefit than treat-none or treat-all scheme by decision curve analysis in both training and testing datasets. Conclusion: Pretreatment radiomics are helpful to predict atypical responses to ICI across tumor types. The combined RS outperformed those from either intra- or peri-tumoral alone which may provide a more comprehensive characterization of atypical responses to ICI. Keywords: radiomics, CT, peritumoral, immune checkpoint inhibitor, atypical responses